Analisis Laporan Keuangan Pengelolaan Limbah Kelapa Sawit Pada PT. Perkebunan Nusantara III Persero Labuhanbatu Selatan - Dharma, Budi; Pratiwi, Ayu Intan; Melati, Melati (Universitas Labuhanbatu, 2022)
Waste/garbage is a by-product or used goods that are considered no longer usable. Waste is generated by various human activities, including those related to industry, transportation, household life, and others. This research was conducted at PT. South Labuhanbatu Nusantara Plantation III (Persero). By using quantitative descriptive techniques, this research strategy. The purpose of the descriptive method is to explain or describe a situation that actually occurs in a business. The cost of handling palm oil mill waste at PT. Perkebunan Nusantara III (Persero) Labuhanbatu Selatan which is discussed by the author of the paper. Definite statistics from PT. Perkebunan Nusantara III (Persero) Labuhanbatu Selatan, which shows that this company is growing every year, is used to produce research conclusions.